The Impact of Breast Mass on Outcomes of Total Skin-Sparing Mastectomy and Immediate Tissue Expander–Based Breast Reconstruction. Issue 3 (March 2015) - Wang, Frederick; Alvarado, Michael; Ewing, Cheryl; Esserman, Laura; Foster, Robert; Sbitany, Hani
Abstract : Background: Larger breast size has been viewed as a relative contraindication for nipple/areola preservation with mastectomy. Few studies have directly evaluated the effect of quantified breast size on postoperative outcomes. Methods: The authors reviewed and assessed 325 total skin-sparing mastectomy cases performed in 224 patients with immediate tissue expander placement that had documented mastectomy specimen mass. Cases were divided into two groups based on having larger (>352 grams) or smaller (⩽352 grams) breast mass. Results: Patients in the larger group had a mean body mass index that was 3.6 kg/m2 greater ( p < 0.001). Overall, the larger group had an 8.1 percent increase in risk of superficial nipple necrosis (adjusted relative risk 4.0; 95 percent CI, 1.5 to 10.3). There were non-significant trends toward a 4.3 percent increase in risk of minor skin necrosis (adjusted relative risk 2.0; 95 percent CI, 0.7 to 6.4) and a 4.4 percent increase in risk of wound breakdown (adjusted relative risk 1.8; 95 percent CI, 0.8 to 3.7) with larger breast mass. Stratifying by radiation exposure, there was a non-significant trend toward a 5.4 percent increase in risk of wound breakdown (adjusted relative risk 2.9; 95 percent CI, 0.9 to 8.8) with larger breast mass in the stratum without radiation exposure. Conclusions: Larger breast mass was associated with an increased risk of superficial nipple necrosis and trends toward increased risks of minor skin necrosis and wound breakdown. Larger breast mass was not associated with an increased risk of nipple or skin flap necrosis requiring operative management. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.